The Bible made impossible : why biblicism is not a truly evangelical reading of Scripture - Smith, Christian, 1960- (Grand Rapids, MI : Brazos, 2012)
"Evangelicalism is cracking apart not because of theological drift to the left but because the only theology that can sustain a genuine evangelicalism is--to use the only word appropriate--a catholic theology. Many who were nurtured in American evangelicalism (as Christian Smith was) and now find it seriously deficient (as Christian Smith does) seem to be those on whom the light has dawned. Here is a genuinely evangelical catholic understanding of scripture." --Scot McKnight, Northern Seminary "Biblicism remains one of the most entrenched and pressing problems facing the church. In his characteristically lucid, direct, and fair-minded fashion, Christian Smith asks questions about biblicism that need to be answered. Smith also begins to articulate an alternative, Christ-centered approach to biblical interpretation that is supremely constructive--a truly evangelical account of scripture." --Douglas A. Campbell, Duke University Divinity School "Given the importance and influence of evangelicalism in American religion and culture, this book is both a healthy corrective and a hopeful sign of positive developments within evangelicalism." --Daniel J. Harrington, SJ, "America " "Ever the sociologist, Smith forces readers to confront and account for the stubborn fact that not everyone who ascribes supreme authority to 'what the Bible says' hears God saying the same thing. Even those, like me, who are not persuaded by his 'truly evangelical' alternative will benefit from this strong dose of realism about the way in which evangelicals actually interpret and appeal to the Bible." --Kevin J. Vanhoozer, Trinity Evangelical Divinity School "[A] finely constructed volume. . . . Smith makes a persuasive case for shifting one's focus from the sole authority of the words of scripture to the one whom scripture proclaims to be 'the way, the truth and the life.' Such a shift, he insists, is necessary for American evangelicalism to move forward." --"Publishers Weekly "
Biblicism and the problem of pervasive interpretive pluralism -- The extent and source of pervasive interpretive pluralism -- Some relevant history, sociology, and psychology -- Subsidiary problems with biblicism -- The Christocentric hermeneutical key -- Accepting complexity and ambiguity -- Rethinking human knowledge, authority, and understanding.
Includes bibliographical references (p. 179-211) and index.
Keywords: Bible -- Evidences, authority, etc; Bible -- Hermeneutics; Evangelicalism